X-ray micro-computed tomography (μCT) evaluation of bubble structure to determine quality of dough and bread made from roasted wheat flour - Germishuys, Zandre (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhDFoodSc)--Stellenbosch University, 2021.